Tax Competition, Investment Irreversibility and the Provision of Public Goods - Michele Moretto; Paolo Panteghini; Sergio Vergalli (Center for Economic Studies and ifo Institute (CESifo), 2013)
This article studies the effects of tax competition on the provision of public goods under business risk and partial irreversibility of investment. As will be shown, the provision of public goods changes over time and also depends on the business cycle. In particular, under source-based taxation, public goods can be optimally provided during a downturn, in the short term. The converse is true during a recovery, when they are underprovided. In the long term however, tax competition does not affect capital accumulation and therefore, the provision of public goods.
Keywords: H25; H32; 330; irreversibility; risk; short- and long-term effects; tax competition